Admixture Mapping of Sepsis in European Individuals With African Ancestries - Hernandez-Beeftink, Tamara; Marcelino-Rodríguez, Itahisa; Guillen-Guio, Beatriz; Rodríguez-Pérez, Héctor; Lorenzo-Salazar, Jose M.; Corrales, Almudena; Díaz-de Usera, Ana; González-Montelongo, Rafaela; Domínguez, David; Espinosa, Elena; Villar, Jesús; Flores, Carlos (Frontiers in Medicine, 2022)
Sepsis is a severe systemic inflammatory response to infections that is accompanied by organ dysfunction. Despite the ancestral genetic background is a relevant factor for sepsis susceptibility, there is a lack of studies using the genetic singularities of a recently admixed population to identify loci involved in sepsis susceptibility. Here we aimed to discover new sepsis loci by completing the first admixture mapping study of sepsis in Canary Islanders, leveraging their distinctive genetic makeup as a mixture of Europeans and African ancestries. We used a case-control approach and inferred local ancestry blocks from genome-wide data from 113,414 polymorphisms genotyped in 343 patients with sepsis and 410 unrelated controls, all ascertained for grandparental origin in the Canary Islands (Spain). Deviations in local ancestries between cases and controls were tested using logistic regressions, followed by fine-mapping analyses based on imputed genotypes, in silico functional assessments, and gene expression analysis centered on the region of interest. The admixture mapping analysis detected that local European ancestry in a locus spanning 1.2 megabases of chromosome 8p23.1 was associated with sepsis (lowest p=1.37x10-4; Odds Ratio [OR]=0.51; 95%CI=0.40-0.66). Fine-mapping studies prioritized the variant rs13249564 within intron 1 of MFHAS1 gene associated with sepsis (p=9.94x10-4; OR=0.65; 95%CI=0.50-0.84). Functional and gene expression analyses focused on 8p23.1 allowed us to identify alternative genes with possible biological plausibility such as defensins, which are well-known effector molecules of innate immunity. By completing the first admixture mapping study of sepsis, our results revealed a new genetic locus (8p23.1) harboring a number of genes with plausible implications in sepsis susceptibility.